What nonopiate medications are effective for pain control in patients with chronic pancreatitis?. Issue 4 (April 2018) - Owoyemi, Kristie Driver; Coulter, Lois; Hudson, Jonell; Vaughn, Brittany
Abstract : EVIDENCE‐BASED ANSWER : Pregabalin reduces pain scores by 12% in patients with chronic pancreatitis (SOR: B, single small RCT). Methionine‐containing antioxidants lead to almost twice as many patients without pain compared with control, but equivocal differences in actual pain scores (SOR: B, meta‐analysis of RCTs and observational trials). Pancreatic enzymes have inconsistent effects on pain (SOR: C, systematic review of conflicting RCTs).